Functional interaction of fibroblast growth factor 8b and androgen in prostate cancer cell proliferation - Wen-jun Xiao; Gui-ming Zhang; Ding-wei Ye (Tumor Biology)
Fibroblast growth factor 8b and androgen play important roles in cell proliferation of prostate cancer. We investigated the effects of fibroblast growth factor 8b and androgen on the proliferation of prostate cell lines and the corresponding intracellular mechanisms. It is found that dihydrotestosterone and fibroblast growth factor 8b stimulated Lncap cell mitosis in a concentration-responsive manner, with 30 ng/mL as the most suitable concentration, respectively. Dihydrotestosterone treatment alone did not enhance the expression and phosphorylation level of fibroblast growth factor receptor but significantly enhanced the level of fibroblast growth factor receptor phosphorylation elicited by fibroblast growth factor 8b. Phosphorylations of extracellular signal–regulated kinase, p38, and c-Jun NH2-terminal kinase were stimulated by dihydrotestosterone or fibroblast growth factor 8b. Among these major downstream pathways for mitogen-activated protein kinase, c-Jun NH2-terminal kinase signaling was most significantly enhanced. Protein kinase C phosphorylation was higher than AKT by the combined stimulation of dihydrotestosterone and fibroblast growth factor 8b. The phosphorylation of CDC2 was significantly induced by dihydrotestosterone and fibroblast growth factor 8b synergetically, and Smad underwent the same induction as CDC2. So the promoting effect of fibroblast growth factor 8b on cell cycle might contribute to the G2/M transition. This study indicated that the functional interaction between fibroblast growth factor 8b and androgen was essential for the prostate cancer cell proliferation.